Stress Intensity Factors - T-Stresses - Weight Functions - Fett, Theo (Schriftenreihe des Instituts für Keramik im Maschinenbau - IKM, 2008)
Failure of cracked components is governed by the stresses in the vicinity of the crack tip. The singular stress contribution is characterised by the stress intensity factor K, the first regular stress term is represented by the so-called T-stress. Sufficient information about the stress state is available, if these two parameters are known Results for K and T are compiled in form of figures, tables, and approximate relations.